Трудно быть фотомоделью: [роман] / Елена Богатырева - Богатырева Елена (Огни большого города, 2001)
Экземпляры: ф.3 (2003) / Инвентарный номер: 47508 / Цена: / Сис.шифр: 84(2Рос=Рус)6-44 / Авт.знак: Б 73 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44